2009
DOI: 10.1055/s-2008-1038725
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Needs during Hospitalization in a Cardiac Surgery Unit before and after Coronary Artery Bypass Graft Surgery

Abstract: The results indicate that preparation for surgery should be conducted very carefully without time pressure. Patients should receive more detailed information on prescribed drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…These information needs would be most relevant to patients in the predischarge period to manage their care at home (Galloway et al. 1995, Jacobs 2000, Henderson & Chien 2004, Krannich et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These information needs would be most relevant to patients in the predischarge period to manage their care at home (Galloway et al. 1995, Jacobs 2000, Henderson & Chien 2004, Krannich et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…), the changes in needs before and after CABG surgery (Krannich et al . ) and changes in needs at different times after CABG surgery (Lie et al . ).…”
Section: Background and Significancementioning
confidence: 99%
“…Moreover, Krannich et al . () examined patients' needs and changes in these needs during hospital stay two days before and 10 days after CABG surgery. The findings of this study revealed that the score of the item ‘information on the correct handling of drugs’ was significantly higher 10 days after CABG surgery compared with two days before surgery.…”
Section: Background and Significancementioning
confidence: 99%
“…Nurses may consider incorporating individualized patient education into their plan of care. [18] Krannich et al [24] countered a study related to patients' needs during hospitalization in a cardiac surgery unit before and after CABG surgery. According to results of this study, it was found that before CABG, patients rated the need for "preparation for surgery", and after CABG the need for "information about the correct handling of drugs", as most important.…”
Section: Discussionmentioning
confidence: 99%